Pathogenic Germline Variants in Cancer Susceptibility Genes in Children and Young Adults With Rhabdomyosarcoma. (2021) - Kim, Jung; Light, Nicholas; Subasri, Vallijah; Young, Erin L.; Wegman-Ostrosky, Talia; Barkauskas, Donald A.; Hall, David; Lupo, Philip J.; Patidar, Rajesh; Maese, Luke D.; Jones, Kristine; Wang, Mingyi; et al.
Abstract : PURPOSE: Rhabdomyosarcoma (RMS) is the most common pediatric soft-tissue sarcoma and accounts for 3% of all pediatric cancer. In this study, we investigated germline sequence and structural variation in a broad set of genes in two large, independent RMS cohorts. MATERIALS AND METHODS: Genome sequencing of the discovery cohort (n = 273) and exome sequencing of the secondary cohort (n = 121) were conducted on germline DNA. Analyses were performed on 130 cancer susceptibility genes (CSG). Pathogenic or likely pathogenic (P/LP) variants were predicted using the American College of Medical Genetics and Genomics (ACMG) criteria. Structural variation and survival analyses were performed on the discovery cohort. RESULTS: We found that 6.6%-7.7% of patients with RMS harbored P/LP variants in dominant-acting CSG. An additional approximately 1% have structural variants ( ATM, CDKN1C ) in CSGs. CSG variants did not influence survival, although there was a significant correlation with an earlier age of tumor onset. There was a nonsignificant excess of P/LP variants in dominant inheritance genes in the patients with FOXO1 fusion–negative RMS patients versus the patients with FOXO1 fusion–positive RMS. We identified pathogenic germline variants in CSGs previously ( TP53, NF1, DICER1, mismatch repair genes), rarely ( BRCA2, CBL, CHEK2, SMARCA4 ), or never ( FGFR4 ) reported in RMS. Numerous genes ( TP53, BRCA2, mismatch repair) were on the ACMG Secondary Findings 2.0 list. CONCLUSION: In two cohorts of patients with RMS, we identified pathogenic germline variants for which gene-specific therapies and surveillance guidelines may be beneficial. In families with a proband with an RMS-risk P/LP variant, genetic counseling and cascade testing should be considered, especially for ACMG Secondary Findings genes and/or with gene-specific surveillance guidelines.